EFFORTS TO IMPROVE EMPLOYEE PERFORMANCE AT FINTECH COMPANIES THROUGH DISCIPLINE AND WORK MOTIVATION - Sutrisno Sutrisno; Juliani Pudjowati; Susi Tri Wahyuni; Ali Ikhwan; Ferdinandus Sampe (SEAN Institute, 2022)
The goal of this study is to determine the effect of work discipline and motivation on employee performance. This study employs a quantitative approach via a Likert scale. This research method employs quantitative research by distributing/questionnaires to determine the validity and reliability of the problems under investigation. Data was gathered by first observing, then interviewing, and finally distributing the final questionnaire and documentation. The obtained data were then analyzed using pre-test and main-test calculations of the data obtained from the field using the SPSS application. The study concludes that the independent variables are work discipline and motivation, and the dependent variable is employee performance.